Industrial Workers’s Regarding Compliance with the Use of Personal Protective Equipment: A Cross-Sectional Study - nofilia sacharum; Khusnul Khotimah (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction: Workplace safety remains a critical issue, and using Personal Protective Equipment (PPE) is essential to reducing occupational hazards. Employee attitudes are important in shaping safety behaviors and compliance with protective measures. Objectives: This study examined the relationship between employee attitudes and compliance with PPE use among workers in a manufacturing company. Methods: A cross-sectional observational study was conducted with 35 employees selected through purposive sampling. Data were collected using two validated questionnaires: one assessing employee attitudes toward PPE use (10 items, Likert scale) and another evaluating PPE compliance (8 items, 0–3 scale). Based on median values, scores were categorized as positive or negative attitudes and compliant or non-compliant behavior. Data were analyzed using frequency distributions and the Chi-Square test. Results: Most participants were male (71.4%) and aged 30–39 (42.8%). 57.1% of respondents reported positive attitudes toward PPE use, while 51.4% demonstrated compliance. Bivariate analysis showed a significant association between employee attitudes and PPE compliance (p = 0.002), with 75% of workers with positive attitudes adhering to PPE protocols compared to 20% with negative attitudes. Conclusions: Positive safety attitudes were strongly linked to higher PPE compliance, emphasizing the need to integrate behavioral and organizational interventions alongside technical measures to promote workplace safety. Although the study provides valuable insights, its cross-sectional design and small sample size limit generalizability. Future studies should adopt longitudinal approaches and include diverse populations to guide targeted safety strategies.